2006
DOI: 10.1021/je060235b
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Partitioning Studies of Bovine Serum Albumin in Mixture of (Poly(ethylene glycol) + K2HPO4 + H2O)

Abstract: Secondary structural changes and partitioning process of bovine serum albumin (BSA) in the mixture of (poly-(ethylene glycol 2000) + K 2 HPO 4 + H 2 O) have been studied at 23°C. The effect of varying weight percents of poly(ethylene glycol) and K 2 HPO 4 on the secondary structure of partitioned BSA and the partitioning process of BSA were examined. The equilibrium weight percents of the obtained aqueous two-phase system (ATPS) have been evaluated, and the phase diagrams including the tie lines are presented.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 25 publications
1
4
1
Order By: Relevance
“…That is what we call the salting-out effect, when you salt something, the salt molecules move from the bottom up and this happens to the proteins as well. In contrast to what is shown in this work, [40] and [41] had a conflicted opinion when they concluded that increasing PEG concentration levels had a beneficial effect on Rec% and K which are increased according to PEG increment. The most hydrophobic anions or cations will tend to spread out in the most hydrophobic phase, while co-ions, which are less hydrophobic, will spread out in the hydrophilic phase.…”
Section: Concentration Effect Of Pegcontrasting
confidence: 99%
See 2 more Smart Citations
“…That is what we call the salting-out effect, when you salt something, the salt molecules move from the bottom up and this happens to the proteins as well. In contrast to what is shown in this work, [40] and [41] had a conflicted opinion when they concluded that increasing PEG concentration levels had a beneficial effect on Rec% and K which are increased according to PEG increment. The most hydrophobic anions or cations will tend to spread out in the most hydrophobic phase, while co-ions, which are less hydrophobic, will spread out in the hydrophilic phase.…”
Section: Concentration Effect Of Pegcontrasting
confidence: 99%
“…After pH 8 the system lost the two-phase formation and specifically in pH 8.3. [22,25,31,40,44,47,48] all had a good agreement with our investigation, while [20,49] had different results according to their studies for different ATPS systems. They went with an opinion that negatively charged protein molecules partition to the bottom phase at high pH, because of the negative net charge of the protein, which has a pI of 4.7.…”
Section: Ph Effectsupporting
confidence: 79%
See 1 more Smart Citation
“…In these works, they found that the partitioning of these two enzymes largely depends on the weight fractions of polymer and salt in feed as well as the molecular weight of polymer; however, the temperature has very limited effect on their partitioning. Faravash et al conducted structural and partitioning studies of bovine serum albumin in an ATPS of PEG2000 + K 2 HPO 4 + H 2 O, and the results indicate that the partition coefficient of this biomolecule increases with the increase in the tie-line length (TLL) of ATPS. Taghavivan and Pazuki investigated the cefalexin partitioning in biocompatible ATPS formed by Tween 20 and different inorganic salts (MgSO 4 and Na 2 SO 4 )/organic salt (Na 3 C 6 H 5 O 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies [10][11][12][13][14][15] show that protein distribution is a function of diverse factors such as: polymer molar mass, polymer concentrations, pH, ionic species, hydrophobic groups and temperature. The study of these operational variables is necessary for the design and scale increase of separation processes.…”
Section: Introductionmentioning
confidence: 99%